The Influence of Sporulation Conditions on the Spore Coat Protein Composition of Bacillus subtilis Spores - Abhyankar, Wishwas R.; Kamphorst, Kiki; Swarge, Bhagyashree N.; van Veen, Henk; van der Wel, Nicole N.; Brul, Stanley; de Koster, Chris G.; de Koning, Leo J. (Frontiers in Microbiology, 2016)
Spores are of high interest to the food and health sectors because of their extreme resistance to harsh conditions, especially against heat. Earlier research has shown that spores prepared on solid agar plates have a higher heat resistance than those prepared under a liquid medium condition. It has also been shown that the more mature a spore is, the higher is its heat resistance most likely mediated, at least in part, by the progressive cross-linking of coat proteins. The current study for the first time assesses, at the proteomic level, the effect of two commonly used sporulation conditions on spore protein presence. 14N spores prepared on solid SG agar plates and 15N metabolically labelled spores prepared in shake flasks containing MOPS buffered defined liquid medium differ in their coat protein composition as revealed by LC-FT-MS/MS analyses. The former condition mimics the industrial settings while the latter conditions mimic the routine laboratory environment wherein spores are developed. As seen previously in many studies, the spores prepared on the solid agar plates show a higher thermal resistance than the spores prepared under liquid culture conditions. The 14N: 15N isotopic ratio of the 1:1 mixture of the spore suspensions exposes that most of the identified inner coat and crust proteins are significantly more abundant while most of the outer coat proteins are significantly less abundant for the spores prepared on solid SG agar plates relative to the spores prepared in the liquid MOPS buffered defined medium. Sporulation condition-specific differences and variation in isotopic ratios between the tryptic peptides of expected cross-linked proteins suggest that the coat protein cross-linking may also be condition specific. Since the core dipicolinic acid content is found to be similar in both the spore populations, it appears that the difference in wet heat resistance is connected to the differences in the coat protein composition and assembly. Corroborating the proteomic analyses, electron microscopy analyses show a significantly thinner outer coat layer of the spores cultured on the solid agar medium.